THE EFFECTIVENESS OF EVENT PROMOTION BY USING SOCIAL MEDIA - Lim, Jason (Universiti Malaysia Sarawak (UNIMAS), 2016)
This study was conducted to investigate the effectiveness of event promotion by using social media. The data collection method that used in this research was quantitative method. The sample sizes of this survey are 200 respondents from the event’s participations. The sampling method used in this research is simple random sampling which tends to minimize bias. Quantitative data have been analyzed by using Statistical Package of the Social Sciences (SPSS) Version 22.0 and Microsoft excel. Types of analysis that have been used in this research are reliability, frequency, multiple responses, cross-tabulation, compare mean, regression, and correlation analysis. The finding result show that Facebook is the social media that has the highest number of users and most effective in promoting events. Beside, the result also shows that the information about the event posted on social media are reliable and the advertisement on social media is more interesting and interactive as compared to traditional media